Exposure to Selenium, Arsenic, Cadmium and Mercury from seafood in the Icelandic population based on Total Diet Studies methodology - Lilja Rut Traustadóttir 1986- (2016)
Background: One of the most important public health responsibilities is to regularly assess dietary exposure to undesirable substances and make policy changes with the aim to decrease exposure accordingly. Seafood is an important source of nutrients in the diet but it can also be a source of exposure for undesirable substances. Aim: To estimate the exposure of the general population in Iceland to selenium, arsenic, cadmium and mercury from seafood and to compare the exposure to health-based guidance values (HBGV). Special focus was put on the exposure assessment of women of childbearing age. Methods: Total Diet Study (TDS) methodology was applied as a part of TDS-Exposure, a European research project. The food selection was based on national food consumption data (FCD), representing the usual diet for the Icelandic population (18-81 years old). The food was collected as sold in the market, prepared as consumed and analyzed. The estimated dietary exposure was then calculated by combining concentration data from the food analyzed and FCD of the same food items. In total 18 seafood samples were analyzed in Iceland, for selenium, arsenic, cadmium and mercury. Results: The median estimated dietary exposure to selenium was 24.96 µg/day from seafood, which is approximately half of the recommended intake. While, only 0.2% of the general population was found to exceed the upper intake level of 300 µg/day. Median arsenic exposure in the general population, represented 4.31 µg/kg b.w./day from seafood. There is no HBGV available for total arsenic exposure. No participant exceeded the tolerable weekly intake (TWI) for cadmium through seafood consumption. As methylmercury is the main form of mercury in seafood the results from total intake were compared to the TWI of methylmercury, which was exceeded by 6% of the general population and 4% of females of childbearing age. The key contributors to methylmercury for participants above the TWI were fermented shark, big halibut fillet and canned tuna in brine. Conclusions: Exposure ...